Uji Organoleptik Dan Mikrobiologi Classic Enzim Belimbing Wuluh (Averrhoa bilimbi L.) - Utari Agustina; Muhammad Iskandar Hakim (Universitas PGRI Palembang, 2023)
Indonesia is a rich country in sources of medicinal plants that can be easily obtained. the belimbing wuluh through the fermentation to turn the raw material into a classic enzyme. the purpose of this research are to make classic enzyme and hand sanitizer from belimbing wuluh, identify the lactic acid bacteria(BAL) from the fermentation of classic enzim belimbing wuluh, and to know the effectiveness of handsanitizer belimbing wuluh. The implementations of the research are preparation of raw materials, to make classic enzyme with anaerobic fermentation method, and laboratory analysis of organoleptic and microbiology tests. The results of the reseach are classic enzim and hand sanitizer products, the identification of lactic acid bacteria (BAL), and the effectiveness of hand sanitizer.from this research, it is known that the process of making the classic enzyme is done by fermentation for three months or 90 days with the composition 1:3:10. The results of this research are the lactic acid bacteria (BAL) is not identified. it because of pH 1,96 and the liquid has been convered into alcohol, the effectiveness of handsanitizer is quite good depend on morphology and ALT tests. The number of colonies formed on sampel after applied hand sanitizer was not found.